2022
DOI: 10.1021/acssensors.2c00121
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Approach Electrochemical Surface-Enhanced Raman Scattering Detection of Mycobacterium tuberculosis in Patient-Derived Biological Specimens: Proof of Concept for a Generalizable Method to Detect and Identify Bacterial Pathogens

Abstract: The recent surge in infectious disease-causing pathogens, resulting in global catastrophe, has merited a pivotal quest toward point-of-care (POC) diagnostics. Mycobacterium tuberculosis (MTB) is still the top bacterium-based infectious disease-causing pathogen worldwide. In a concerted effort toward simplifying and decentralizing the discriminatory screening of MTB causing pathogens, electrochemical surface-enhanced Raman scattering (EC-SERS) was adopted to create a customized screening tool. The development s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The Raman spectra of all samples display a weak peak at approximately 520 cm − 1 , corresponding to the Si substrate. The peaks around 500, 592, 611, 667, 740, 773, 861, 885, and 948 cm − 1 represent the different vibrational modes of MB [23][24][25][26][27][28][29]. The peak around 1620 cm − 1 , corresponding to stretching c-c ring, is the signature Raman peak of MB [30].…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectra of all samples display a weak peak at approximately 520 cm − 1 , corresponding to the Si substrate. The peaks around 500, 592, 611, 667, 740, 773, 861, 885, and 948 cm − 1 represent the different vibrational modes of MB [23][24][25][26][27][28][29]. The peak around 1620 cm − 1 , corresponding to stretching c-c ring, is the signature Raman peak of MB [30].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the current CAST-R cost per sample for susceptibility testing for two drugs at four different concentrations is approximately $8 (The cost of the required D 2 O is $2, Raman testing is $5, and other experimental materials is $1), a substantially lower cost than that of conventional AST conducted using the broth dilution method ($15 for mycobacterial susceptibility testing of two drugs). Specially, it has been widely reported for the detection of Mycobacterium tuberculosis via Raman Microspectroscopy [ 28 30 ]. Thus, the CAST-R may also apply to Mycobacterium tuberculosis which brings greater economic benefits and time savings.…”
Section: Discussionmentioning
confidence: 99%
“…In another application, electrochemical-SERS (EC-SERS) approach has been successfully applied for the detection of TB . 129 For example, Karaballi et al reported an EC-SERS DNA aptasensor platform for the label-free SERS detection of TB DNA biomarker in urine. 130 They used a cost-effective carbon screen printed electrode modified with AgNPs.…”
Section: Sers Applications For the “Big 5” Antibiotic Resistance Chal...mentioning
confidence: 99%